Meet the Guest Editor - Farinas, Edgardo T. (Combinatorial Chemistry & High Throughput Screening, 2006)
Dr. Edgardo T. Farinas did his undergraduate work at Loyola University of Chicago (B.S. in 1990) and pursued graduate studies in bioinorganic chemistry at the University of California at Santa Cruz (Ph.D. in 1997) under Pradip Mascharak. After postdoctoral studies with Lynne Regan at Yale University, Frances Arnold at the California Institute of Technology, and Brent Iverson and George Georgiou at University of Texas at Austin, he joined the New Jersey Institute of Technology faculty as an Assistant Professor of Chemistry. His research has focused on the interface between chemistry, biology, and engineering. His current research interests are in engineering proteins using directed evolution and rational approaches. The goals include developing high-throughput screening technologies to assay mutant enzyme libraries to discovery novel biocatalyst, combining rational and directed evolution approaches to create de novo enzymes, metabolic pathway engineering in bacteria, novel protein display technologies, and incorporation of non-natural amino acids in proteins. SELECTED PUBLICATIONS [1] Alcalde, M.; Farinas, E.T.; Arnold, F.H. J. Biomolecular Screen., 2004, 9, 141-146. [2] Farinas, E.T.; Alcalde, M.; Arnold, F.H. Tetrahedron, 2003, 60, 525-528. [3] Glieder, A.; Farinas, E.T.; Arnold, F.H. Nat. Biotechnol., 2002, 20, 1135-1139. [4] Farinas, E.T.; Schwaneberg, U.; Glieder, A.; Arnold, F.H. Advanced Synthesis and Catalysis, 2001, 343, 601-606. [5] Schwaneberg, U.; Otey, C.; Cirino, P.C.; Farinas, E.T.; Arnold, F.H. J. Biomolecular Screen., 2001, 6, 111-118. [6] Farinas, E.T.; Regan, L. Protein Science, 1998, 7, 1939-1946. [7] Farinas, E.T.; Nguyen, C.; Mascharak, P.K. Inorganica Chimica Acta, 1997, 263, 17-21. [8] Farinas, E.T.; Tan, J.D.; Mascharak, P.K. Inorg. Chem., 1996, 35, 2637. [9] Guajardo, R.J.; Chavez, F.; Farinas, E.T.; Mascharak, P.K. J. Am. Chem. Soc., 1995, 117, 3883. [10] Farinas, E.T.; Baidya, N.; Mascharak, P.K. Inorg. Chem., 1994, 33, 5970. [11] Tan, J.D.; Farinas, E.T.; David, S.S.; Mascharak, P.K. Inorg. Chem., 1994, 33, 4295. [12] Farinas, E.T.; Tan, J.D.; Baidya, N.; Mascharak, P.K. J. Am. Chem. Soc., 1993, 115, 2996.